Analytical model for concrete-filled double skin tube columns with different cross-sectional shapes under axial compression. (September 2022) - Li, Zhenlin; Lin, Siqi; Zhao, Yan-Gang
Abstract: The existing theoretical analysis models of concrete-filled double skin tube (CFDST) columns are limited to the analysis of CFDST columns with circular outer and inner tubes (CC-CFDST). The purpose of this paper is to propose a unified model for CFDST columns with different cross-sectional shapes, including CFDST columns with rectangular outer and inner tubes (RR-CFDST), CFDST columns with square outer and inner tubes (SS-CFDST), CFDST columns with square outer and circular inner tubes (SC-CFDST), CFDST columns with circular outer and square inner tubes (CS-CFDST), CC-CFDST columns. The CFDST columns with different shapes (original columns) are replaced with equivalent CC-CFDST columns by assuming that they have the same cross-sectional areas of the inner and outer steel tubes and concrete. The difference in mechanical properties between the original column and the equivalent column is attributed to the difference in the confining effect of the steel tube on the core concrete caused by the different shape, which is considered by the shape effect coefficient k e . The proposed model is verified by collected experimental data of CFDST columns with different cross-sectional shapes. The mean value and coefficient of variation of the ratio of the calculated bearing capacity to the experimental bearing capacity are 1.006 and 0.119, respectively. The results show that the proposed model can predict the axial compression bearing capacity and load–deflection curves of CFDST columns accurately.